Traversing the profile of biomimetically nanoengineered iron substituted hydroxyapatite: synthesis, characterization, property evaluation, and drug release modeling. Issue 35 (25th May 2018) - Sheikh, Lubna; Sinha, Shivendra; Singhababu, Y. N.; Verma, Vineeta; Tripathy, Sucheta; Nayar, Suprabha
Abstract : Heuristic picture connoting the green synthesis of iron substituted hydroxyapatite nanoparticles having versatile properties. Abstract : Even though ion substituted hydroxyapatite nanoparticles are associated with promising features for biomedical applications, green synthesis with precise control of size and shape to produce uniform nanoparticles remains elusive. To overcome this, we herein propose a room temperature, biomimetic approach to synthesize iron substituted nano-hydroxyapatite (m-HA) along with thorough physicochemical and biological evaluation. The study revealed that 10% iron could be isomorphously doped into hydroxyapatite crystal structure. Stress, strain, energy density and atomic occupancy, as a result of substitution, have been ascertained by Williamson-Hall and Rietveld analysis using X-ray diffraction data. X-Ray photoelectron spectroscopy has been employed to confirm the elemental composition, chemical state and environment of m-HA. In addition, vibrating sample magnetometer of m-HA shows a trend towards superparamagnetic behaviour. Further, fluorescence assisted cell sorting and scanning electron microscope studies confirmed increase in the cell density with increasing iron concentration. Excellent antibacterial property, enhanced biocompatibility and bioactivity have also been interestingly observed. More controlled and sustained drug release has been observed with the inclusion of iron. A mathematical model developed to elucidate drug diffusion coefficient reveals Fickian mechanism to govern the release profile up to 8 hours followed by a non-Fickian transport. With these distinct features, this versatile material holds immense potential as bone repair material for osteoporosis where targeted delivery of calcium is required, as a heating mediator in cancer treatment and as a vehicle for site specific delivery of drug.